Epigenetic regulation of the secreted frizzled-related protein family in human glioblastoma multiforme - Schiefer, L.; Visweswaran, Malini; Perumal, Vanathi; Arfuso, Frank; Groth, David; Newsholme, Philip; Warrier, Sudha; Dharmarajan, Arunasalam (Nature Publishing Group, 2014)
Glioblastoma multiforme (GBM) are intracranial tumors of the central nervous system and the most lethal among solid tumors. Current therapy is palliative and is limited to surgical resection followed by radiation therapy and temozolomide treatment. Aberrant WNT pathway activation mediates not only cancer cell proliferation but also promotes radiation and chemotherapeutic resistance. WNT antagonists such as the secreted frizzled-related protein (sFRP) family have an ability to sensitize glioma cells to chemotherapeutics, decrease proliferation rate and induce apoptosis. During tumor development, sFRP genes (1–5) are frequently hypermethylated, causing transcriptional silencing. We investigated a possible involvement of methylation-mediated silencing of the sFRP gene family in human GBM using four human glioblastoma cell lines (U87, U138, A172 and LN18). To induce demethylation of the DNA, we inhibited DNA methyltransferases through treatment with 5-azacytidine. Genomic DNA, RNA and total protein were isolated from GBM cells before and after treatment. We utilized bisulfite modification of genomic DNA to examine the methylation status of the respective sFRP promoter regions. Pharmacological demethylation of the GBM cell lines demonstrated a loss of methylation in sFRP promoter regions, as well as an increase in sFRP gene-specific mRNA abundance. Western blot analysis demonstrated an increased protein expression of sFRP-4 and increased levels of phosphorylated-ß-catenin. These data indicate an important role of methylation-induced gene silencing of the sFRP gene family in human GBM.